Seismicity and development of Romashkino hydrocarbon field’s Almetyevskaya area - I. N. Ognev; A. I. Stepanov (Georesursy, 2024)
The relationship between the various human activities and seismic activity has become more evident in the last several decades. One of the important domains where such a relationship manifests itself is hydrocarbon fields’ development. South East Tatarstan (Russia) is a region where the link between seismicity and the development of the giant Romashkino hydrocarbon field has been established. The goal of the current study is to conduct the causative analysis between the seismic activity and the development of the Romashkino hydrocarbon field’s Almetyevskaya area which is located in the most seismically active zone of the southeastern Tatarstan.